Impact of smoking on survival in nasopharyngeal carcinoma: A cohort study with 23, 325 patients diagnosed from 1990 to 2016. (September 2021) - Sun, Xue-Song; Xie, Si-Yi; Luo, Dong-Hua; Liu, Li-Ting; Guo, Shan-Shan; Liu, Sai-Lan; Tang, Lin-Quan; Chen, Qiu-Yan; Mai, Hai-Qiang
Highlights: From 1990 to 2016, the smoking rate of patients showed a downward trend, while the overall survival improved over time. The 5-year OS rates in the entire cohort were 76.4%, 68.9%, and 79.8% in the former, current, and never smokers. In the multivariate analysis of the IMRT cohort, the risk of death and metastasis was higher in the current smokers. Heavy smoking increases the risk of death and metastasis. Abstract: Background: We aimed to compare the survival outcomes of patients with nasopharyngeal carcinoma (NPC) who had different smoking behaviors and were treated with two- or three-dimensional radiotherapy (2D/3DRT) or intensity-modulated radiotherapy (IMRT) with a long-term follow up. Methods: From 1990 to 2016, 23, 325 patients with NPC were included. The primary endpoint of this study was overall survival (OS). The log-rank test and Cox proportional hazards regression model were used to assess the patients' survival outcomes. Results: The 5-year OS rates in the entire cohort were 76.4%, 68.9%, and 79.8% in the former, current, and never smokers, respectively. In the IMRT cohort, the OS rates showed the same trend. Compared with the never smokers, the 5-year distant metastasis-free survival (DMFS) was lower in the former ( P = 0.004) and current smokers ( P < 0.001). In the multivariate analysis of the IMRT cohort, the risk of death ( P = 0.003) and recurrence ( P = 0.027) was higher in the current smokers, while the risk of metastasis was higher in the former and current smokers ( P = 0.031 and P = 0.019, respectively) than the never smokers. A total of 53.9% of the effect of smoking status on OS was through sex, age, and Epstein-Barr virus DNA, which were significant mediators. Conclusion: In the IMRT era, being a former smoker or current smoker was an independent risk factor for DMFS. The difference in OS and locoregional relapse-free survival was significant only between the current smokers and never smokers.